Bond–Slip Law Between Steel Bar and Different Cement-Based Materials Considering Anchorage Position Function - Xiao, Jie; Long, Xiang; Ye, Ming; Jiang, Haibo; Liu, Lingfei; Mo, Fan; Deng, Dejun; Huang, Zikang (Frontiers in Materials, 2021)
The bond performance between steel bar and cement-based materials was the prerequisite for the two materials to work together. Previous studies showed that the tensile strength and strain capacity of the matrix had a major impact on the bonding performance. Therefore, the bond behavior of the steel bars in Engineered Cementitious Composites (ECC) may be different from the bond behavior of the steel bars in traditional brittle materials (such as normal concrete and steel fiber reinforced concrete). For this reason, this paper adopted twelve direct pullout tests specimens including three types of concrete, two types of steel bars. The strain of the steel bar at six measuring points was measured with strain gauge. Based on the measured strain and free end slip of the steel bars, the distribution of steel stress, bond stress, relative slip and the bond slip relation along the anchorage length were obtained and analyzed for different concrete and different steel bars. Based on these test results of steel strain and relative slip at six measuring points, the anchorage position function could be established in consideration of anchorage position, which was conducive to the establishment of an accurate bond-slip relationship. In addition, it found that the calculation formula of critical anchorage length in the current Code for Design of Concrete Structures (GB 50010-2010) in China was safe and conservative to calculate the critical anchorage length of the steel bar in ECC. It is suggested to establish the critical anchorage length formula suitable for ECC in future studies.